2019
DOI: 10.1002/mnfr.201900632
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Face of Cereals: Wheat‐Derived Prebiotics Counteract the Detrimental Effect of Gluten on Metabolic Homeostasis in Mice Fed a High‐Fat/High‐Sucrose Diet

Abstract: Scope: Cereals are important sources of carbohydrates, but also contain nutrients that could impact adiposity. The contribution of gluten to obesity and the effects of prebiotics-arabinoxylo-oligosaccharides (AXOS) and fructo-oligosaccharides (FOS)-that can be extracted from gluten-containing cereals are analyzed. Methods and results: Mice are fed a control diet, Western diet (WD, consisting of high fat/high sucrose), or WD with 5% gluten. Prebiotics are tested in the WD with gluten. Gluten does not increase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…We can further speculate that those mechanisms might partially account for the improved glucose tolerance observed in previous study upon supplementation of pasteurized A. muciniphila. 23 We have previously shown that an HFD or a western diet reduces the expression of intectin, [51][52][53] a marker of intestinal epithelial cell renewal. 54 In the present study, we found that the increased energy excretion was accompanied by the restoration of the expression of intectin in the jejunum and increased transcript level of Cyclin D1, another marker of intestinal epithelial turnover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We can further speculate that those mechanisms might partially account for the improved glucose tolerance observed in previous study upon supplementation of pasteurized A. muciniphila. 23 We have previously shown that an HFD or a western diet reduces the expression of intectin, [51][52][53] a marker of intestinal epithelial cell renewal. 54 In the present study, we found that the increased energy excretion was accompanied by the restoration of the expression of intectin in the jejunum and increased transcript level of Cyclin D1, another marker of intestinal epithelial turnover.…”
Section: Discussionmentioning
confidence: 99%
“…54 In the present study, we found that the increased energy excretion was accompanied by the restoration of the expression of intectin in the jejunum and increased transcript level of Cyclin D1, another marker of intestinal epithelial turnover. Interestingly, we previously discovered that the expression of intectin was enhanced following supplementation with oligofructose, 51,53 a prebiotic known to increase the abundance of A. muciniphila in rodents. 51,55 Of note, expression of Cyclin D1, among others, is known to be decreased in absence of gut microbiota, supporting the notion that the gut microbiota is able to affect intestinal cell renewal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction and immunoblotting of protein of interest were performed in liver and gastrocnemius muscle. Total RNA was isolated from different sections of SAT, brown adipose tissue (BAT), liver and skeletal muscle prior reverse transcriptase quantitative PCR (qPCR) analysis 21. The full procedures are detailed in online supplementary information.…”
Section: Methodsmentioning
confidence: 99%
“…And some oligosaccharides can selectively proliferate benecial bacteria and inhibit the growth and reproduction of harmful bacteria, so as to improve the abundance and composition of gut microbiota. 18,19 Meanwhile, functional oligosaccharides can also be fermented by gut microbiota to produce products with biological activities such as SCFAs. Bering 20 found that HMOS can serve as prebiotics and immunomodulators for preterm infants, stimulating gut adaptation and reducing the incidence of necrotizing enterocolitis (NEC).…”
Section: Introductionmentioning
confidence: 99%